Acromion Compromise Does Not Significantly Affect Clinical Outcomes after Reverse Shoulder Arthroplasty: A Matched Case-Control Study. Issue 2 (July 2019) - Werner, Brian C.; Gulotta, Lawrence V.; Dines, Joshua S.; Dines, David M.; Warren, Russell F.; Craig, Edward V.; Taylor, Samuel A.
Background: The effect of a pre-operative compromised acromion on reverse shoulder arthroplasty (RSA) is not well-studied. Purposes/Questions: We sought to determine the effect of a pre-operative compromised acromion on outcomes following RSA. Methods: We conducted a retrospective case-control study of consecutive patients who underwent RSA over a 6-year period (June 2007 to June 2013) with a diagnosis of rotator cuff tear arthropathy. Pre-operative plain radiographs were examined to determine the presence of acromion compromise ( n = 11). Acromion compromise was defined as (1) less than 25% of the normal acromion thickness (8.8 mm), (2) less than 50% of the normal acromion anteroposterior width (46.1 mm), (3) presence of an os acromiale, or (4) presence of acromial fragmentation. An age- and sex-matched control cohort without acromial compromise was also identified ( n = 33). The primary outcome variable was the final minimum 2-year American Shoulder and Elbow Surgeons (ASES) score. Secondary outcomes included final minimum 2-year scores on the 12-Item Short-Form Health Survey (SF-12), with the physical component score (PCS) and mental component score (MCS); 2-year Marx shoulder activity scale scores; and final 2-year satisfaction scores. Results: At 2 years post-operatively, there were no significant differences in final scores using ASES, SF-12 PCS or MCS, or Marx shoulder activity scale. There were no significant differences between groups for satisfaction scores in any of the assessed domains. No complications were reported at 2 years' follow-up in any of the study patients or controls. Conclusions: Between patients with and without pre-operative acromion compromise, there were no differences in clinical outcomes, satisfaction levels, or complication rates after RSA. Our findings suggest that surgeons performing RSA in the setting of pre-operative acromion compromise, including os acromiale, acromial fragmentation, or severe thinning, should not expect poor post-operative clinical outcomes.